1999
DOI: 10.1136/bmj.319.7213.815
|View full text |Cite
|
Sign up to set email alerts
|

Association between breast feeding and asthma in 6 year old children: findings of a prospective birth cohort study

Abstract: (Accepted 2 June 1999)Association between breast feeding and asthma in 6 year old children: findings of a prospective birth cohort study W H Oddy, P G Holt, P D Sly, A W Read, L I Landau, F J Stanley, G E Kendall, P R Burton AbstractObjectives To investigate the association between the duration of exclusive breast feeding and the development of asthma related outcomes in children at age 6 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
200
3
15

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 433 publications
(234 citation statements)
references
References 22 publications
(29 reference statements)
16
200
3
15
Order By: Relevance
“…Thus, the higher risk of atopy and asthma reported in breastfed children might as well be due to the introduction of complementary foods in mixed breastfed children, rather than to breastmilk. In that case, these results would not contradict those of Oddy and colleagues 4 , who showed a protective effect of exclusive breastfeeding against asthma and atopy.…”
Section: /2supporting
confidence: 51%
“…Thus, the higher risk of atopy and asthma reported in breastfed children might as well be due to the introduction of complementary foods in mixed breastfed children, rather than to breastmilk. In that case, these results would not contradict those of Oddy and colleagues 4 , who showed a protective effect of exclusive breastfeeding against asthma and atopy.…”
Section: /2supporting
confidence: 51%
“…Our study for the first time provides an explanation why some studies of breast-feeding have observed a protective effect against asthma and atopy, 13,[22][23][24][25][26][27][28] whereas other studies showed an increased risk. [7][8][9][10][11][12] We are the first to analyze data from early childhood well into middle age.…”
Section: Discussionmentioning
confidence: 70%
“…Several studies 13,[22][23][24][25][26][27][28] and 2 recent meta-analyses 1,2 have reported a protective effect of breast-feeding in the first few years of life. We found exclusive breastfeeding did have a protective effect against risk of current asthma, infantile eczema, and food allergies at 7 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…32 A protective effect from breast-feeding (either any or exclusive breast-feeding and breast-feeding of varying duration) on asthma risk was found in a systematic review of 56 studies. 33 A prospective birth cohort study 34 found a protective effect from exclusive breast-feeding for at least 4 months on asthma risk to age 6 years. On the other hand, the Tucson Children's Respiratory Study 35 found that exclusive breast-feeding was protective against recurrent wheeze in early life but was associated with an increased risk of asthma and recurrent wheeze from age 6 to 13 years, although only in atopic children of asthmatic mothers.…”
Section: Discussionmentioning
confidence: 99%